Study of Spun Pile to Pile Cap Connection with Steel Jacket Strengthening - Hugen, Stevany Lydia Jedidjah; Orientilize, Mulia; Prakoso, Widjojo Adi; Lase, Yuskar (ASTONJADRO, 2023)
Spun piles in Indonesia are designed to behave as an elastic structure according to SNI8460:2017. The piles are designed with low confinement where the amount does not meet ASCE 7-16 requirements. Indonesia should apply a performance-based design for the bottom structure someday since the seismic demand tends to increase based on the current seismic risk map. Steel jackets are proposed to fulfill the need for transverse reinforcement, particularly at the connection region where the curvature demand is higher. The steel jacket was made from high-quality zincalume steel, a high-quality rolled steel that is customizable following the size of the spun pile and has a low cost. Experimental and numerical studies were conducted. A 500mm diameter spun pile was retrofitted with a steel jacket loaded vertically and horizontally. The experimental study applied the cyclic loading according to ACI374.2r, and 0.1fc’Ag vertical load was applied. The experimental study applied the cyclic loading according to ACI374.2r, and 0.1fc’Ag vertical load was applied. The experimental study found that the spun pile and grouted concrete interaction was not perfectly bonded. A further finite element study was conducted to understand the connection’s performance thoroughly. Two parameters were investigated, the steel jacket’s height and thickness. A numerical study performed pushover analysis on the 3D model using the ABAQUS software to see the effect of the height and moment-curvature analysis obtained from fiber section element from SAP software to study the impact of the thickness. The results were presented in terms of its strength and ductility.